COMPARATIVE STUDY OF PAIN KILLER DRUGS EFFECTS AFTER THE DENTAL IMPLANT PLACEMENT IN THE ACTIVE ADULT POPULATION - Ruxandra Nicolette Voinea Georgescu; Cristian Niky Cumpătă; Mihaela Răescu; Mircea Gheorghiţă; Andreea Gabriela Nicola; Dana Cosac (Amaltea Medical Publishing House, 2019)
There is controversy in recent studies on the use of NSAIDs used to control pain and swelling after the insertion of dental implants that may interfere with the osteointegration process. The purpose of this study is to compare the effect of tramadol versus codeine in pain management after the insertion of dental implants. In conclusion, according to this study, tramadol - containing analgesics are significantly more effective than those containing codeine / caffeine in reducing postoperative pain. It was also found that the selected group of analgesics containing codeine / caffeine were significantly more effective than those containing tramadol in reducing swelling, which was reported to be significantly lower in the first 3 days in the codeine / caffeine group. As a result, codeine / caffeine-containing analgesics are effective and acceptable in reducing pain and inflammation.